Comparison of the immunogenicity of BNT162b2 and CoronaVac COVID‐19 vaccines in Hong Kong - Mok, Chris Ka Pun; Cohen, Carolyn A.; Cheng, Samuel M. S.; Chen, Chunke; Kwok, Kin‐On; Yiu, Karen; Chan, Tat‐On; Bull, Maireid; Ling, Kwun Cheung; Dai, Zixi; Ng, Susanna S.; Lui, Grace Chung‐Yan; et al. (Respirology (Carlton, Vic.), 2022)
Background and objective Few head‐to‐head evaluations of immune responses to different vaccines have been reported. Methods Surrogate virus neutralization test (sVNT) antibody levels of adults receiving either two doses of BNT162b2 (n = 366) or CoronaVac (n = 360) vaccines in Hong Kong were determined. An age‐matched subgroup (BNT162b2 [n = 49] vs. CoronaVac [n = 49]) was tested for plaque reduction neutralization (PRNT) and spike‐binding antibody and T‐cell reactivity in peripheral blood mononuclear cells. Results One month after the second dose of vaccine, BNT162b2 elicited significantly higher PRNT50, PRNT90, sVNT, spike receptor binding, spike N‐terminal domain binding, spike S2 domain binding, spike FcR binding and antibody avidity levels than CoronaVac. The geometric mean PRNT50 titres in those vaccinated with BNT162b2 and CoronaVac vaccines were 251.6 and 69.45, while PRNT90 titres were 98.91 and 16.57, respectively. All of those vaccinated with BNT162b2 and 45 (91.8%) of 49 vaccinated with CoronaVac achieved the 50% protection threshold for PRNT90. Allowing for an expected seven‐fold waning of antibody titres over 6 months for those receiving CoronaVac, only 16.3% would meet the 50% protection threshold versus 79.6% of BNT162b2 vaccinees. Age was negatively correlated with PRNT90 antibody titres. Both vaccines induced SARS‐CoV‐2‐specific CD4+ and CD8+ T‐cell responses at 1 month post‐vaccination but CoronaVac elicited significantly higher structural protein‐specific CD4+ and CD8+ T‐cell responses. Conclusion Vaccination with BNT162b2 induces stronger humoral responses than CoronaVac. CoronaVac induces higher CD4+ and CD8+ T‐cell responses to the structural protein than BNT162b2. Through the head‐to‐head comparison, vaccination with BNT162b2 induces significantly higher levels of SARS‐CoV‐2‐specific binding and neutralizing antibody responses compared to CoronaVac. CoronaVac induces higher CD4+ and CD8+ T‐cell responses to the structural protein than BNT162b2. See related Editorial